2015
DOI: 10.1310/sci2102-156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adult Romantic Attachment and Social Support on Resilience and Depression in Individuals with Spinal Cord Injuries

Abstract: Background:Spinal cord injury (SCI) can cause psychological consequences that negatively affect quality of life. It is increasingly recognized that factors such as resilience and social support may produce a buffering effect and are associated with improved health outcomes. However, the influence of adult attachment style on an individual's ability to utilize social support after SCI has not been examined. Objective: The purpose of this study was to examine relationships between adult romantic attachment, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…The total score can range from 0 to 27, where higher scores represent a higher depressive mood. The PHQ-9 has been standardized with sound psychometric properties [ 16 , 22 ] and Cronbach’s alpha was 0.87 in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score can range from 0 to 27, where higher scores represent a higher depressive mood. The PHQ-9 has been standardized with sound psychometric properties [ 16 , 22 ] and Cronbach’s alpha was 0.87 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies revealed that self-efficacy, social support [ 13 , 19 ], and spirituality [ 11 , 20 , 21 ] enhanced resilience in persons with SCI, whereas depression/depressive mood [ 6 , 11 , 16 , 19 ], stress, anxiety, and internal locus of control [ 6 ] impeded resilience of those individuals. Previous findings regarding the influence of demographic and injury-related factors on resilience are still inconclusive [ 6 , 13 , 16 , 22 ]. Most of the aforementioned factors were also found to affect resilience in individuals surviving earthquakes or other disasters [ 17 , 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some contributing variables included family relationships, social support, and resilience (16)(17)(18)(19)(20). Active coping strategies have been found to have a strong impact on individual variance in positive recovery outcomes in patients (20,21).…”
Section: Does Resilience Matter In Spinal Cord Injury (Sci)?mentioning
confidence: 99%
“…4 Higher resilience is consistently associated with strong self-efficacy, greater perceived social support and stable mood. 4, 5,9 Resilience can vary among individuals based on the presence of different factors. 10,11 Personal demographic and injury-related factors were found to be associated with resilience among individuals with SCI 12,13 and survivors of earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Nevertheless, some studies reported a non-significant association between resilience and demographic and injury-related factors. 4,5,9,12,16 Hence, there are inconclusive findings on the demographic and injury-related variables contributing to resilience. Resilience is dynamic in nature; therefore, a cross-sectional study might not represent a holistic picture.…”
Section: Introductionmentioning
confidence: 99%